Ecgto reperfusion time analysis ant its impact in the prognosis of acute myocardial infarction. (26th April 2021) - Oliveira, CC; Braga, C; Medeiros, P; Campos, I; Pires, C; Mane, F; Flores, R; Azevedo, P; Pereira, M; Gaspar, A
Abstract: Funding Acknowledgements: Type of funding sources: None. INTRODUCTION: According to 2017 ESC guidelines for STEMI, reperfusion time of patients not admitted in centers with primary PCImust be ≤120 minutes (min). OBJECTIVE: To analyze the proportion of patients with STEMI admitted in hospitals without primary PCI in which reperfusion time was ≤120 min and to understand its prognostic impact. METHODS: Multicentric, retrospective study. 1909 STEMI pts with <12h of symptoms evolution, admitted in hospitals without primary PCI betweenOctober 2010 and September 2019 who underwent primary PCIwere analyzed. Patients were studied according to the ECG-reperfusion time: ≤120 min (Group 1 – G1) or >120 min (Group 2 – G2). RESULTS: G1 corresponded to 42.5% while G2 to 57, 5%. In both groups patients were mainly male. G1 1 was younger (61 ± 13 vs 64 ± 14, p < 0.001) and had more prevalence of smoker patients (44.1% vs 36.1%, p < 0.001). G2 have more often diabetes (25.9 % vs 21.2%, p = 0.02). Time until the 1 st medical contact and admission was longer inG2 (120 min vs 105 min, p = 0.004). "Via verde coronária"was more frequently activated inG1 (5.5% vs 1.8%, p < 0.001). There were no significant differences on the KK classification on admission, but G2 had more prevalence of severe left ventricular disfunction (LVEF ≤ 30%: G1 = 3%, G2 = 6%, p = 0.002). During the hospitalization, G2 had significantly higher rates of heart failure (11.7% vs 17.4%, p < 0.001) and cardiogenic shock (3.6% vs 5.7%, p = 0.036). Cardiac arrest on admission was more prevalent inG2 (3% vs 5.2%, p = 0.017). Mortality during hospitalization was higher inG2 (1.6 vs 4.2%, p < 0.001). Patients admitted on North were mainly inG2 (n = 493, 39.6% vs 60.4%) as on Center (n = 253, 25.7% vs 74.3%) and South (n = 304, 35.3% vs 64.7%). In Lisbon and Tejo Valley patients were mainly onG1 (n = 860, 51.6% vs 48.4%). Follow-up was performed in 859 patients (G1 = 42.6% vs G2 = 54.4%). After 1 year, there were no differences in mortality (G1 = 16 deaths, G2 = 26 deaths, p = 0.520). Cardiovascular and noncardiovascular readmissions were also not difference between the groups mortality (p = 0.782 and p = 0.548, respectively). CONCLUSION: Most of the patients did not comply the current guidelines. Reduction of system delay in STEMIremains crucial, since lower reperfusion time have less in-hospital complications and mortality. Follow-up was not performed in all patients which can justify the results. This work shows that it is fundamental to adopt organizational measures to reduce system delay.